2021
DOI: 10.1002/dc.24859
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of “atypia” in thyroid fine‐needle aspiration specimens

Abstract: The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) provided a standardized framework for resulting thyroid fine‐needle aspiration (FNA) specimens and introduced the low‐risk category of atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS). This indeterminate category has significantly evolved over time with the incorporation of molecular testing, reclassification of noninvasive follicular thyroid neoplasm with papillary‐like nuclear features (NIFTP), and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…[18][19][20] The reported ranges of ROM associated with each TBSRTC diagnostic category have been consistent except in the so-called indeterminate diagnoses, especially AUS/FLUS. 18,21 At the time of the first edition of TBSRTC (2010), the estimated ROM of the cases diagnosed as AUS/FLUS ranged from 5% to 15%, and by the time of the second edition (2017), had increased to 10%-30%. 4,15 As defined in TBSRTC, AUS/FLUS includes a heterogeneous group of thyroid lesions that are difficult to classify into a more definitive category.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] The reported ranges of ROM associated with each TBSRTC diagnostic category have been consistent except in the so-called indeterminate diagnoses, especially AUS/FLUS. 18,21 At the time of the first edition of TBSRTC (2010), the estimated ROM of the cases diagnosed as AUS/FLUS ranged from 5% to 15%, and by the time of the second edition (2017), had increased to 10%-30%. 4,15 As defined in TBSRTC, AUS/FLUS includes a heterogeneous group of thyroid lesions that are difficult to classify into a more definitive category.…”
Section: Discussionmentioning
confidence: 99%
“…TBSRTC played an important role in standardizing diagnostic terminology, facilitating communication among cytopathologists and clinicians, and improving the clinical management of patients with thyroid nodules 18–20 . The reported ranges of ROM associated with each TBSRTC diagnostic category have been consistent except in the so‐called indeterminate diagnoses, especially AUS/FLUS 18,21 . At the time of the first edition of TBSRTC (2010), the estimated ROM of the cases diagnosed as AUS/FLUS ranged from 5% to 15%, and by the time of the second edition (2017), had increased to 10%–30% 4,15 .…”
Section: Discussionmentioning
confidence: 99%
“…The Advances in Health Sciences Research, volume 46 risk of malignancy related to the nuclear atypia rather than architectural atypia. Previous study showed that the presence of 2 nuclear features will increase the risk of malignancy up to 30-33% and will reach up to 100% when 4 nuclear features appeared [6,7] The AUS category comprises a heterogeneous group of findings, and the risk of malignancy associated with the nature of the observed atypia [8]. Most guidelines have recommended close follow-up for the AUS and repeating USG-guided FNA [7].…”
Section: Discussionmentioning
confidence: 99%
“…For this entity to remain a valid and valuable category, AUS should not be over-used. 15 Cases with scant follicular groups trapped in fibrin clots with crowded architecture or focal nuclear pallor should be called non-diagnostic instead of AUS. A cellular aspirate with predominant benign findings and only focal microfollicles should be called benign, not AUS.…”
Section: Differential Diagnosis and Potential Pitfallsmentioning
confidence: 99%